Pembelajaran Bahasa Arab menggunakan Media Strip Story di Mushalla Karang Kates Tlambah Karang Penang Sampang - Hamdy, Mohammad Zainal; Rosi, Fathur; Subairi, Subairi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Learning Arabic in the 21st Century requires creativity and innovation from Arabic teachers to be able to attract students' interest and not be inferior to learning other foreign languages. Mushalla Karang Kates Tlambah Karang Penang Sampang still uses traditional and classic methods. There is a real need to upgrade learning so that students are interested in Arabic, one of which is through strip story media. The research attempts to explain how strip story media is used and how students respond to learning Arabic using this media. This research uses an interpretive paradigm with a qualitative approach, data collection techniques using interviews and direct observation. The results show that Arabic Language Learning using Strip Story Media at Mushalla Karang Kates Tlambah Karang Penang Sampang consists of Preparation, Implementation and Closing. After implementing this lesson, the students' response was very good and enthusiastic, especially in learning Arabic